UNIT 8.20 Expression Data Analysis with Reactome. Issue 1 (9th March 2015) - Jupe, Steve; Fabregat, Antonio; Hermjakob, Henning
Abstract : The Reactome database of curated biological pathways provides a tool for visualizing user‐supplied expression data as an overlay on pathway diagrams, thereby affording an effective means to examine expression of the constituents of the pathway and determine whether all that are necessary are present. Several experiments can be visualized in succession, to determine whether expression changes with experimental conditions, a useful feature for examining a time‐course, dose‐response, or disease progression. © 2015 by John Wiley & Sons, Inc.